3D heat flow effects in the imaging of subsurface graphical features in semi-transparent media by pulsed thermography. (November 2021) - Caruso, G.; Mercuri, F.; Zammit, U.; Paoloni, S.; Ceccarelli, S.; Orazi, N.
Highlights: Detection of hidden texts buried into paper based cultural heritage artefacts. Analysis of the 3D heat diffusion in optically semi-transparent materials. Study of the distortions in the thermographic images of subsurface graphic features. Abstract: Pulsed thermography has proven to be a useful tool to detect subsurface features in ancient bookbindings and, in particular, to provide the IR image of texts buried beneath the end- leaves of the books. In this paper the theory is presented to analyze the influence of the geometrical and physical parameters involved in the processes leading to the distortion in the IR image of the detected buried graphical features. The distortion is mainly due to the lateral diffusion of the heat generated at the ink feature after the absorption of an excitation light. A comprehensive analysis taking into account the three dimensional heat diffusion process, in an optically semi-transparent medium, is considered. Numerical results are reported showing the behavior of the contrast and of a distortion parameter of the buried inked feature detected by the IR imaging in the various considered cases.